2003
DOI: 10.1017/s0954579403000440
|View full text |Cite
|
Sign up to set email alerts
|

False belief understanding in maltreated children

Abstract: False belief understanding was investigated in maltreated (N = 203), low socioeconomic status (SES) nonmaltreated (N = 143), and middle SES nonmaltreated (N = 172) 3- to 8-year-old children. Contrasts among the three groups provided an opportunity to examine the impact of family contextual influences on theory of mind development. Specifically, child maltreatment served as an “experiment of nature” in order to elucidate theory of mind abilities. Two false belief tasks and language assessments were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 11 publications
10
121
0
11
Order By: Relevance
“…Consistent with this, Bouchard et al [51] found a significant correlation between attachment security and mentalization as operationalized by reflective functioning (RF), and Simons et al [52] found low attachment security to be associated with low self-esteem and reduced mentalization. Childhood maltreatment was also associated with delayed theory of mind development, which can be seen as a prerequisite for mentalization [53] and low RF [20]. Deficient mentalization capabilities are associated with behavioral disorders, antisocial behavior, and increased externalizing behavior, specifically aggressive behavior [13,51,54,55,56].…”
Section: Attachment and Mentalizationmentioning
confidence: 99%
“…Consistent with this, Bouchard et al [51] found a significant correlation between attachment security and mentalization as operationalized by reflective functioning (RF), and Simons et al [52] found low attachment security to be associated with low self-esteem and reduced mentalization. Childhood maltreatment was also associated with delayed theory of mind development, which can be seen as a prerequisite for mentalization [53] and low RF [20]. Deficient mentalization capabilities are associated with behavioral disorders, antisocial behavior, and increased externalizing behavior, specifically aggressive behavior [13,51,54,55,56].…”
Section: Attachment and Mentalizationmentioning
confidence: 99%
“…Play is also affected in the context of traumatic experience (Alessandri, 1991;Cunningham, Fill, & Al-Jamie, 1999;Fonagy & Target, 2000). In addition, abuse and neglect are associated with a range of sociocognitive difficulties, including deficits in theory of mind and emotional understanding (Cicchetti, Rogosch, Maughan, Toth, & Bruce, 2003;de Rosnay et al, 2008), as well as with a reduced lexicon for describing internal states (Beeghly & Cicchetti, 1994). It is likely that the neurophysiological effects of trauma, including hypervigilance and the activation of primitive prementalizing systems developed to detect potential threat, undermine mentalization and cognitive development.…”
Section: Mentalization and Reflective Functioningmentioning
confidence: 99%
“…There is increasing evidence from both clinical and nonclinical samples that adverse childhood experiences are associated with deficits in social cognitive processes such as emotion perception and theory of mind (Barahal et al 1981;Cicchetti et al 2003;Pears & Fisher, 2005;Koizumi & Takagishi, 2014). Social cognitive deficits are a core impairment of borderline personality disorder and are thought to be worsened by childhood maltreatment (Roepke et al 2013).…”
Section: Neurocognitive and Social Cognitive Impairmentmentioning
confidence: 99%